Applicability of the cycling power profile field test for determining training zones - Rauter, S.; Maretic, L.; Iskra, S.; Milic, R. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
Introduction In road cycling, advanced monitoring of load and effort during training and competition is used extensively. Various laboratory and field tests are used to determine training zones in cycling. One common method is an incremental laboratory test to determine physiological thresholds that help predict performance. The protocol used depends on threshold being targeted, whether it's the lactate threshold or the ventilation threshold. In addition, training zones can be determined by analyzing the power profile, characterized by two key parameters: the critical power (CP) and the W', the latter representing the maximum power sustained above the CP and usually associated with anaerobic capacity.